Enhanced Mobility Solution In Mobile Ipv6 Network - David, Adeniji Oluwashola (2008)

(untitled)
The performance of Network Mobility (NEMO) used to manage network mobility does not provide satisfactory result in terms of delay, throughput and session continuity when dealing with multihomed mobile network. Enhanced Mobility Solution in Mobile IPv6 Network is extremely complex; the study addressed the multihoming issues of MIPV6 Networks on the basis of NEMO Basic Support, analyzes the benefits of multihoming and discusses implementation issues of all classes of multihoming possibilities. Additionally, Policy-based routing, as one of the multihoming benefits, is studied in particular. A framework based on policy based routing protocol was proposed for handling both the inbound and the outbound traffic on a mobile network, under specified policies which consider packet characteristics, current network situation and user preferences. The interface selection algorithm was based on NEMO implementation structure using a technique of mutihoming which was extended to MIPv6 concepts The outcome of this research work are: a designed policy protocol for policy messages communication between the Mobile Router and the Home Agent, the framework is simulated using Network Simulator (NS2) with an extension of mobiwan, the result shows the end to end delay, average end to end delay, overhead, optimal routing path, average inter-packet latency and throughput of the developed system. The information from the analysis of the result shows that the enhanced solution has drastically reduced average packet delay to minimum with 72.5 %( 0.040s to 0.011s), and end-end delay with 75 %( 0.020s to 0.005s) compared with NEMO solution. Overhead in the mobile network was maintained by 10bytes per nested level by keeping the session. The solution is important by enterprises in making decision to acquire internet connectivity for the purpose of connectivity redundancy and traffic load distribution optimization. This result is very important for time sensitive application that requires stable network condition.